Evaluating wetland assets in consumptive and non-consumptive dimensions and utilization potentials in Ibeno, Akwa Ibom state, Nigeria - Comfort M Abraham; Mbuotidem S Ebong; Joseph C Udoh; Nyeti-Obong I William (Global Journal of Ecology - Peertechz Publications, 2021)
Wetlands possess abundant valuable environmental resources which hold possible opportunities for rapid and sustainable development of the eco-communities. This paper seeks to highlight multifunctional benefits derived from consumptive and non-consumptive wetland resources in Ibeno, Akwa Ibom State with a view to mitigating under-utilization and unsustainable exploitation for effective management in the area. Field reconnaissance survey identified 8 sampled communities which were purposively selected in which 400 copies of structured questionnaires were distributed to generate database for the study. It was hypothesized that tapping into the multi-utilization potentials of consumptive and non-consumptive wetland resources will not contribute to local livelihood and socio-economic development of the region. The chi-square analysis at 0.05 level of significance confirmed 45.23 greater than 2.13. This affirmed the multi-utilization potentials of consumptive and non consumptive wetland resources livelihood opportunities by way of job creation, source of food, source of protein, provision of building materials for constructions, provision of medicinal and pharmaceutical material of plant and animal origin among others. The result showed that the spheres of socio-economic development in Ibeno are not only dependent on crude-oil exploitation but also on the sustainable utilization of other wetland resources in the area. The underutilization is caused by the interplay of natural factors like the swampy nature of the environment, coastal topography lying towards the sea shore with waterlogged and wave action; and anthropogenic forces. Therefore, it was recommended that wetland resources require sustainable exploitation and management for the protection of diverse resources for continuous utilization by all.